Perceptions of Present and Future Capability among a Sample of Rural British Columbia Youth - Kapil, Meg E.; Shepard, Blythe C. (Canadian Journal of Counselling and Psychotherapy, 2011)
A cross-sectional survey explored 96 rural adolescents’ perceptions of their rural context and how their self-concept is related to perceptions of capability regarding hopes and fears for the future. The youth surveyed, from the Kootenay Boundary region of British Columbia, indicated ambivalence about staying in their communities after leaving high school, although many generally liked living there. Findings reveal a positive correlation between a high estimation of capability for obtaining a future hoped-for self and a high self-concept rating. This result has implications for rural youth, including building self-esteem through fostering perceptions of capability and increasing community engagement.